Why Are We Scientists? Drawing Inspiration From Rita Levi-Montalcini - Malerba, Francesca (Frontiers in Cellular Neuroscience, 2022)
In 2007, drawing inspiration from her previous experiments on chick embryos, Rita Levi-Montalcini, at the age of 99, proposed a new project, and a research group, in which I was included, was formed at the European Brain Research Institute (EBRI). Looking back on this experience, I can say that Professor Levi-Montalcini’s approach and the relationships she formed with my colleagues and me, contributed to my growth as a researcher. With her welcoming and warm-hearted disposition, she taught me how to consider other people’s ideas without prejudice, to reason and not to exclude any hypothesis. I also learned from her how to overcome those difficulties that are so frequent in the research field, always keeping in mind the starting point and looking towards the objective, with a factual optimism. I was just a young researcher and deeply flattered that a Nobel Laureate, with an incredible career and extraordinary life, treated me as her equal. My experience with Professor Levi-Montalcini has also provided me with a reliable path to follow, and when I encounter difficulties and challenges, I ask myself what would she have done. This approach has always helped me to move forward. Indeed, I believe the best way to celebrate Rita Levi-Montalcini as a woman in neuroscience is to recount how her exceptional example is a constant reminder as to why I have chosen to be a scientist. I hope she will always continue to be a source of inspiration for scientists in the future.